1992
DOI: 10.1111/j.1365-2125.1992.tb04112.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid concentrations of paracetamol after a single intravenous dose of propacetamol.

Abstract: Since the antipyretic and probably the analgesic effects of paracetamol are, at least in part, centrally mediated, its plasma and cerebrospinal fluid (CSF) concentrations were measured in 43 patients with nerve-root compression pain. Each subject was given a short i.v. infusion of 2 g propacetamol, a prodrug which is hydrolysed to paracetamol within 7 min. Single blood and CSF samples were drawn concomitantly in each patient at intervals between 20 min and 12 h. Maximum CSF drug concentrations were observed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(111 citation statements)
references
References 18 publications
9
95
0
7
Order By: Relevance
“…To avoid this slow and erratic uptake of oral acetaminophen in postsurgical patients, IV acetaminophen (paracetamol) has been used in Europe since 2001. PK studies of IV acetaminophen have demonstrated rapid CNS penetration in both adult and pediatric patients [5,6]. Recently, a comparative study of IV versus oral or rectal administration of acetaminophen demonstrated more rapid CNS drug concentrations and overall higher CNS exposure (area under the curve) for the IV route, based on cerebral spinal fluid sampling in six healthy male volunteers [7].…”
Section: Non-opioid Adjuvantsmentioning
confidence: 99%
“…To avoid this slow and erratic uptake of oral acetaminophen in postsurgical patients, IV acetaminophen (paracetamol) has been used in Europe since 2001. PK studies of IV acetaminophen have demonstrated rapid CNS penetration in both adult and pediatric patients [5,6]. Recently, a comparative study of IV versus oral or rectal administration of acetaminophen demonstrated more rapid CNS drug concentrations and overall higher CNS exposure (area under the curve) for the IV route, based on cerebral spinal fluid sampling in six healthy male volunteers [7].…”
Section: Non-opioid Adjuvantsmentioning
confidence: 99%
“…Paracetamol and NSAI drugs are well known for their effectiveness and have good safety profiles. Their individual use or combinations with opioids provide effective pain control for postoperative pain management [5,6]. The exact action mechanism of paracetamol has not been completely explained, however, it is thought to have an indirect effect on the serotonergic system through central COX3 inhibition of the central nervous system (CNS) [7].…”
Section: Introductionmentioning
confidence: 99%
“…A gram of propacetamol infused intravenously hydrolyzes into 0.5 g of acetaminophen and pharmacologically inactive N,N-diethylglycine within 7 min [13][14][15]. Acetaminophen is widely used to control mild to moderate pain in clinical conditions and is well known for its inhibitory effect on central cyclooxygenase.…”
mentioning
confidence: 99%